Complexity and energy saving in cloud load balancing algorithms: a study - Sahu, Babuli; Swain, Sangram Keshari (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Based on the idea of pay-per-use and on-demand access to shared IT resources, cloud computing is rapidly emerging as a computing model of choice. It holds ample promises for individual users and organizations as well as impacts significantly the IT industry as a whole. Consequently, there is a pertinent demand for large, high performance and efficient data centers. These data centers necessitate energy efficient cloud computing algorithms to reduce energy consumption and diffusion of carbon dioxide. This paper follows a systematic approach to review energy consumption algorithms used in cloud data centers. Although several studies are available in the literature, it is felt that more exhaustive study is required to present the stat-of-the-art in the field. Further, the paper identifies the most common factors such as the technique used by the researchers, resources on which they focused, strength, weakness, the complexity of algorithm and percentage of energy saving resulted by the algorithms and presents a comparative assessment of some select algorithms. This will certainly help the new researchers for a comprehensive understanding of the issues in cloud computing energy saving algorithms and set path for further study.